BEHAVIOURS OF ENGINEERING PROPERTIES OF ACACIA HYBRID UNDER COPPER CHROME ARSENIC (CCA) TREATMENT AT DIFFERENT AGE GROUPS - ELLYNE, ENDUAT (Universiti Malaysia Sarawak (UNIMAS), 2018)
This paper aim is to determine the behaviour of engineering properties of Acacia hybrid under copper chrome arsenic (CCA) at air-dry condition of different age groups. The engineering properties are determined by conducting three (3) mechanical strength tests namely; a) shear parallel to grain test, b) tensile parallel to grain test and c) cleavage test. The specimens for these three tests are divided into two (2), one is for controlled specimens, and the other one is for treated specimens. The specimens are treated to evaluate the performance of Acacia hybrid under CCA treatment. Also, the tests are conducted in both direction of tangential and radial for shear parallel to grain test and cleavage test. The specimens are tested in small clear size as stated in British Standard (BS 373: 1957). For 7-year-old, the average values strength for shear parallel to grain, tensile parallel to grain and cleavage are 16.00 MPa (radial) and 17.06 MPa (tangential), 141.80 MPa, and 13.67 N/mm (radial) and 15.82 N/mm (tangential) for controlled specimens and 16.78 MPa (radial) and 17.52 MPa (tangential), 158.40 MPa, and 14.61 N/mm (radial) and 16.69 N/mm (tangential) for treated specimens respectively. For 10-year-old, of controlled specimens, the average values of strength for shear parallel to grain, tensile parallel to grain and cleavage are 17.46 and 18.18 MPa (radial and tangential), 148.99 MPa, and 15.00 and 17.66 N/mm (radial and tangential) and 17.92 and 18.59 MPa (radial and tangential), 176.44 N/mm and 16.41 and 18.21 N/mm (radial and tangential) for treated specimens respectively. Meanwhile for 13-year-old, the results are 16.62MPa and 17.61 MPa for radial and tangential planes, 144.19 MPa, and 14.19 N/mm and 16.19 N/mm (radial and tangential) for controlled specimens and 16.88 and 17.67 MPa (radial and tangential), 160.26 MPa, and 15.41 N/mm and 16.86 N/mm (radial and tangential) for treated specimens respectively. The conclusion drawn that 10-year-old Acacia hybrid exhibits the highest strength on shear parallel to grain, tensile parallel to grain and cleavage followed by 13- and 7-year-old. The treated specimens seemed to perform slightly better than that of the controlled specimens.